Supported to perform: sports bras and breast volume do not impair cycling performance in females - Illidi, Camilla R.; Jensen, Dennis (Frontiers in Sports and Active Living, 2024)
Introduction Despite the importance of sports bras for comfort during exercise in people with breasts, concerns persist regarding their potential effects on athletic performance. Discrepancies in previous studies necessitate a closer examination of the interaction between sports bras, breast volume, exertional symptoms, and exercise performance. Methods Twenty-three recreationally-active, normal bodyweight females completed three 10-km time-trials on a cycle ergometer on three separate occasions in a randomized order, while wearing a professionally fitted high-support sports bra, a professionally fitted low-support sports bralette, or a personal, self-selected sports bra. Performance was quantified as the time to complete the 10-km distance. Cardiorespiratory and symptom responses were measured throughout. Results Participants were grouped by their estimated breast volumes (small: mean ± SD 284 ± 38 ml, median bra size: 32C; large: 560 ± 97 ml, 34DD; p = 0.002, g = 3.84). The average time-trial duration was 23.1 ± 3.1 min and comparable across breast volume groups and sports bra conditions (between-group: p = 0.794, ηp2 < 0.01; between-bras: p = 0.273, ηp2 < 0.01). Notably, larger-breasted participants experienced stronger symptoms of chest tightness (p = 0.042, ηp2 = 0.18), which were associated with their ratings of perceived exertion and breathlessness (intensity and unpleasantness). Irrespective of breast volume, the high-support sports bra also evoked stronger symptoms of chest tightness (p = 0.039, ηp2 = 0.15). Discussion Stronger symptoms of chest tightness associated with larger breast volumes or high-support sports bras do not impede performance during self-paced non-weight-bearing exercise in recreationally-active females.